Samuel Smith family papers - Smith, Samuel, 1752-1839.; Smith, John Spear, -1866.; Smith, Robert, 1757-1842.
Correspondence, letterbooks, military and political papers, notebooks, diaries, financial and legal papers, writings, printed matter, and other papers. Papers (1772-1850) of Samuel Smith relate to such topics as affairs of the U.S. Senate, public finance and the Bank of the United States, trade and tariffs, relations with Great Britain and France, Fort McHenry and the defense of Baltimore during the War of 1812, and history and politics of Maryland; papers (1804-1867) of John Spear Smith document his diplomatic service in Russia and Great Britain and Confederate military activities in Virginia during the Civil War; and papers (1796-1830) of Robert Smith pertain primarily to his real estate investments in Baltimore. Other Smith family papers relate chiefly to personal and business matters but include an account of the 1st Battle of Bull Run, 1861.
Correspondents include John Quincy Adams, Nicholas Biddle, James Brown, John C. Calhoun, Churchill Caldom Cambreleng, Henry Clay, William Harris Crawford, Albert Gallatin, Christopher Hughes, Andrew Jackson, Thomas Jefferson, Joseph Kent, Edward Livingston, James Madison, Louis McLane, James Monroe, John Montgomery, Robert Morris, John Nelson, Robert Carter Nicholas, Wilson Cary Nicholas, William Pinkney, Thomas Jefferson Randolph, Richard Rush, Jonathan Russell, Robert Carter Smith, Aaron Vail, Martin Van Buren, James Wilkinson, and Levin Winder.
Microfilm edition of most of the collection available
Microfilm edition produced from originals in the Manuscript Division.
U.S. senator and representative from Maryland, U.S army officer, and mayor of Baltimore, Md. Other family members represented include Samuel Smith's son John Spear Smith, diplomat; and brother Robert Smith, U.S. secretary of state and businessman of Baltimore, Md.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John Quincy, -- 1767-1848 -- Correspondence; Biddle, Nicholas, -- 1786-1844 -- Correspondence; Brown, James, -- 1766-1835 -- Correspondence; Calhoun, John C. -- 1782-1850 -- Correspondence; Cambreleng, Churchill Caldom, -- 1786-1862 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Crawford, William Harris, -- 1772-1834 -- Correspondence; Gallatin, Albert, -- 1761-1849 -- Correspondence; Hughes, Christopher, -- 1786-1849 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Kent, Joseph, -- 1779-1837 -- Correspondence; Livingston, Edward, -- 1764-1836 -- Correspondence; Madison, James, -- 1751-1836 -- Correspondence; McLane, Louis, -- 1786-1857 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Montgomery, John, -- 1764-1828 -- Correspondence; Morris, Robert, -- 1734-1806 -- Correspondence; Nelson, John, -- 1791-1860 -- Correspondence; Nicholas, Robert Carter, -- 1728-1780 -- Correspondence; Nicholas, Wilson Cary, -- 1757-1820 -- Correspondence; Pinkney, William, -- 1764-1822 -- Correspondence; Randolph, Thomas Jefferson, -- 1792-1875 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Russell, Jonathan, -- 1771-1832 -- Correspondence; Smith, Robert Carter -- Correspondence; Vail, Aaron, -- 1796-1878 -- Correspondence; Van Buren, Martin, -- 1782-1862 -- Correspondence; Wilkinson, James, -- 1757-1825 -- Correspondence; Winder, Levin, -- 1757-1819 -- Correspondence; Smith family; Confederate States of America. -- Army; United States. -- Congress. -- Senate; Bank of the United States (1816-1836); Bull Run, 1st Battle of, Va., 1861.; Diplomatic and consular service, American -- Great Britain; Diplomatic and consular service, American -- Russia; Finance, Public -- United States; Real estate investment -- Maryland -- Baltimore; Tariff -- United States; Baltimore (Md.) -- History -- War of 1812.; Fort McHenry (Baltimore, Md.); France -- Foreign relations -- United States; Great Britain -- Foreign relations -- United States; Manassas (Va.) -- History -- Civil War, 1861-1865.; Maryland -- History; Maryland -- History -- War of 1812.; Maryland -- Politics and government; United States -- Commerce; United States -- Foreign relations -- France; United States -- Foreign relations -- Great Britain; United States -- Politics and government -- 1783-1865.; Virginia -- History -- Civil War, 1861-1865.; Army officers; Mayors -- Maryland -- Baltimore; Representatives, U.S. Congress -- Maryland; Senators, U.S. Congress -- Maryland